2012
DOI: 10.1016/j.bandc.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Sentence processing in Lewy body spectrum disorder: The role of working memory

Abstract: Prior work has related sentence processing to executive deficits in non-demented patients with Parkinson’s disease (PD). We extended this investigation to patients with dementia with Lewy bodies (DLB) and PD dementia (PDD) by examining grammatical and working memory components of sentence processing in the full range of patients with Lewy body spectrum disorder (LBSD). Thirty-three patients with LBSD were given a two-alternative, forced-choice sentence-picture matching task. Sentence type, working memory, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 95 publications
0
21
0
2
Order By: Relevance
“…In addition, metaregression showed an increased probability of finding brain atrophy in left superior temporal gyrus in patients with lower MMSE scores, which further confirmed that lateral temporal lobe was implicated in DLB. Abnormalities in the lateral temporal lobe including the superior and middle temporal cortex are coincident with the findings of some researches through other neuroimaging methods such as functional MRI (fMRI) [28], resting state fMRI [29,30], 3D brain single photon emission computed tomography (SPECT) [31], cortical GM thickness analysis [32], and cortical pattern matching [33]. The superior temporal sulcus (STS) is the fissure that separates the superior and middle temporal gyrus, which plays a crucial role in auditory-visual integration.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, metaregression showed an increased probability of finding brain atrophy in left superior temporal gyrus in patients with lower MMSE scores, which further confirmed that lateral temporal lobe was implicated in DLB. Abnormalities in the lateral temporal lobe including the superior and middle temporal cortex are coincident with the findings of some researches through other neuroimaging methods such as functional MRI (fMRI) [28], resting state fMRI [29,30], 3D brain single photon emission computed tomography (SPECT) [31], cortical GM thickness analysis [32], and cortical pattern matching [33]. The superior temporal sulcus (STS) is the fissure that separates the superior and middle temporal gyrus, which plays a crucial role in auditory-visual integration.…”
Section: Discussionmentioning
confidence: 53%
“…A meta-analysis of 34 English language dementia studies 14 using cut-off scores ranging from 27/30 to 22/30 concluded that the MMSE was only “modestly effective at ruling-out dementia in specialist settings.” In a recent meta-study, Pinto et al 11 concluded that 80% of the included 34 articles found that the MoCA test was superior to the MMSE test in discriminating between individuals with mild cognitive impairment and no cognitive impairment, while they concluded that both tests were accurate in the detection of Alzheimer’s disease (AD). However, these studies also find that the MMSE has acceptable sensitivity to identify dementia.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, nonfluent aphasia and speech apraxia are well-recognized presentations of CBS and PSP (Kertesz et al, 2000; Rohrer et al, 2010) and may signify a broader spectrum of linguistic dysfunction in this disease group. Whereas CBS is commonly associated with early speech production deficits overlapping with progressive nonfluent aphasia (Kertesz et al, 2000), Parkinson’s disease and DLB may be associated with deficits of sentence processing and verbal working memory (Gross et al, 2012). In principle, linguistic profiles might distinguish diseases with abnormal deposition of synuclein (synucleinopathies: PDD, DLB) (Spillantini et al, 1997) from those with abnormal deposition of tau (tauopathies: CBS, PSP) (Arai et al, 2001) and the heterogeneous other pathologies underpinning CBS and progressive nonfluent aphasia (Kertesz & McMonagle, 2010).…”
Section: Introductionmentioning
confidence: 99%